Enhanced efficiency of melatonin by stepwise-targeting strategy for acute lung injury - Wang, Hongbo; Li, Jing; Jin, Jianbo; Hu, Jingbo; Yang, Chunlin (Frontiers in Bioengineering and Biotechnology, 2022)
Oxidative stress plays a key role in the progress of acute lung injury (ALI), which is an acute, progressive respiratory failure characterized by alveolar capillary injury caused by various external and internal factors other than cardiogenic factors. Pulmonary vascular endothelial cells are the main target cells during ALI, and therefore the mitochondrial targeting antioxidant derivative triphenylphosphine-melatonin (TPP-MLT) was encapsulated in VCAM-1 antibodies-conjugated nanostructured lipid carriers (VCAM@TPP-MLT NLCs) for lung targeting delivery. VCAM@TPP-MLT NLCs could be preferentially internalized by inflammatory endothelial cells in lung tissues, and then the released TPP-MLT from NLCs effectively eliminated the excessive reactive oxide species (ROS) and ameliorated cell apoptosis. Overall, the results suggested that VCAM@TPP-MLT NLCs exhibited remarkable in vitro and in vivo therapeutic effect on ALI, and could be a promising and efficient strategy for the treatment of ALI.